A new type of noncovalent surface–π stacking interaction occurring on peroxide-modified titania nanosheets driven by vertical π-state polarization. Issue 12 (10th February 2021) - Ma, Shenqian; Zhao, Weixin; Zhou, Jun; Wang, Jiaou; Chu, Shengqi; Liu, Zigeng; Xiang, Guolei
Abstract : A new type of noncovalent surface–π stacking interaction occurring on a transition metal oxide, titania, is reported, which is different from the traditional forms on sp 2 -hybridized planar structures like graphene. Abstract : Noncovalent π stacking of aromatic molecules is a universal form of noncovalent interactions normally occurring on planar structures (such as aromatic molecules and graphene) based on sp 2 -hybridized atoms. Here we reveal a new type of noncovalent surface–π stacking unusually occurring between aromatic groups and peroxide-modified titania (PMT) nanosheets, which can drive versatile aromatic adsorptions. We experimentally explore the underlying electronic-level origin by probing the perturbed changes of unoccupied Ti 3d states with near-edge X-ray absorption fine structures (NEXAFS), and find that aromatic groups can vertically attract π electrons in the surface peroxo-Ti states and increase their delocalization regions. Our discovery updates the concept of noncovalent π-stacking interactions by extending the substrates from carbon-based structures to a transition metal oxide, and presents an approach to exploit the surface chemistry of nanomaterials based on noncovalent interactions.